The communication of persons: Kant’s theory of marriage law held captive by pagan anthropology - Sudakov A. (Кантовский сборник, 2013)
The paper analyzes Kant’s philosophy of matrimonial law. It focuses on the idea of this law as “possession of a person as a thing and its use as a person”: Kant conceives marriage as an interpersonal relation in an external form of real possession, in the aspect of the objective and subjective goal of such relation, but primarily in the aspect of its legal and ethical possibility. Given the naturalistic interpretation of the constitutive act for this kind of law, the legal deduction of marriage comes in a desperate contradiction with Kant’s ethics of personal dignity, because it seems to lead to a mutual instrumentalization of persons; as a matter of fact, Kant's deduction of marriage rules out the possibility of mutual personal obligations of family members. The naturalistic premise of Kant's family law, provenient from the ancient Roman property law, is as follows: marriage is mutual possession of the other's person as a thing and the use of it as a person for mutual pleasure; it seems to predetermine a necessary connection between legal use and legal posession of a person, the latter presupposing primary acquisition. This premise causes in Kantian family law an antinomy of private law and personalist ethics, which can hardly be eliminated by the own theoretical means of Kant's legal philiosophy. According to the essentials of Kant's ethics, the dignity of the other person, which is (allegedly) acquisited in matrimony, allows no possible equivalent, and its loss cannot be compensated at all events by the fact of mere mutuality of the instrumentalizing relation. The doubtfulness of this naturalistic premise of Kant's family theory means in terms of legal philosophy the doubtfulness of the premise which states the title-establishing status of primary acquisition in the field of personal law. References to the ethical idea of the absolute unity of personality, as well as the accent on “pleasure” as the necessary subjective goal of marital union, which leads the moralist an the philosopher of law upon a false trail, cannot provide a real solution of the problem. The naturalistic premise, in consequence of which the meaning of love is conceived in terms of pleasure, perpetuates the Roman contractualism in matrimonial law by understanding marriage as an external relation of persons, and prepares the soil for the seeds of a nihilistic philosophy of marriage and family. Kant's opinions about the reasons of inacceptability of false and, as a matter of fact, contractually based forms of matrimonial unions, proceed in undermining still more the basics of his positive philosophy of family, and supply additional arguments for a reform of Kantian philosophy of matrimonial law. In the expositions of Kant’s philosophy of marriage, when purified from this naturalistic premise, there can be traced some more integral notion of family union, seen as a moral unity of persons as such, in regard to which the marriage as external union of physical persons is a mere consequence and legal form. The personal union in matrimonial communication creates a relation in which there are two physical persons, but only one moral personality of the family and one legal person; not only a personal and at the same time property-related union, but a personaltranspersonal union. The specific person as an absolute monadical unity is here absolved by the personality of the family, as the absolute unity of active... between persons, which has no other goal besides of and out of this union itself. When seen that way, it doesn't seem necessary any more to identify the “real-right form” of legal matrimonial union with the essence of the personal union itself, and therefore a merely contractual vision of family law can be overcome. The personalist philosophy of family retains the fruitful contents of Kant's matrimonial law theory: the notion that the matrimonial union is necessary “due to the law of humanity”, and not due to mere natural necessity; the notion of matrimonial acquisition as one accomplished neither factually, nor contractually, but “according to a law”, as a consequence of an obligation to enter a family unity. And yet, just as in Kant’s theory of law there is no ethically enriched concept of this genuine kind of union, in the individual ethics of Kant’s later years there is no ethical notion of family as a personality. Its elaboration became a task for German classical idealism.